2016
DOI: 10.3389/fmicb.2015.01498
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a New M13 Metallopeptidase from Deep-Sea Shewanella sp. E525-6 and Mechanistic Insight into Its Catalysis

Abstract: Bacterial extracellular peptidases are important for bacterial nutrition and organic nitrogen degradation in the ocean. While many peptidases of the M13 family from terrestrial animals and bacteria are studied, there has been no report on M13 peptidases from marine bacteria. Here, we characterized an M13 peptidase, PepS, from the deep-sea sedimentary strain Shewanella sp. E525-6, and investigated its substrate specificity and catalytic mechanism. The gene pepS cloned from strain E525-6 contains 2085 bp and enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Furthermore, two unique genes encoding S8 family peptidase and ATP‐dependent zinc metalloprotease were most similar to those found in Microbacterium sp. Leaf161 from plant sources (Table S4), which could potentially enhance the ability to obtain nutrients from particulate organic nitrogen in sediments, as previously reported (Yang et al., 2015).…”
Section: Resultsmentioning
confidence: 55%
“…Furthermore, two unique genes encoding S8 family peptidase and ATP‐dependent zinc metalloprotease were most similar to those found in Microbacterium sp. Leaf161 from plant sources (Table S4), which could potentially enhance the ability to obtain nutrients from particulate organic nitrogen in sediments, as previously reported (Yang et al., 2015).…”
Section: Resultsmentioning
confidence: 55%
“…Zinc metallopeptidases follow two distinct mechanisms for the cleavage of peptide sequences depending on whether the nucleophile is a water molecule 43 or a Glu residue 44 . Based on our QM/MM metadynamics simulations, we found that AM0627, and likely other mucinases, follow a two-step mechanism in which a nucleophilic water molecule is firstly activated by a Glu residue acting as the catalytic base (Glu326 in AM0626).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the genome included genes encoding metallopeptidases. This cluster of genes plays an important role in the degradation and utilization of organic nitrogen [30]. The most abundant COG categories were 'cell wall/membrane/envelope biogenesis', 'transcription', 'amino acid transport and metabolism', 'carbohydrate transport and metabolism', 'translation, ribosomal structure and biogenesis', and 'replication, recombination and repair' (Fig.…”
Section: Genome Analysis and Phylogenymentioning
confidence: 99%